Catalyst-free regioselective [3+2] cycloadditions of alpha,beta-unsaturated N-arylnitrones with alkenes to access functionalized isoxazolidines: a DFT study - Ghosh, Arnab; Mane, Manoj V.; Rode, Haridas B.; Patil, Siddappa A.; Sridhar, Balasubramanian; Dateer, Ramesh B. (Chemistry-An Asian Journal, 2020)
The catalyst-free regioselective [3+2]-cycloaddition of alpha,beta-unsaturated N-arylnitrones with alkenes are developed. The series of synthetically important functionalized isoxazolidines are prepared in good to excellent yields by step economic pathway under ligand and transition-metal-free conditions. The regioselective cycloaddition pathway supported by control experiment and computational study.
Keywords: DFT study; isoxazolidines; metal and ligand free; nitrone cycloaddition; Regioselective

Aluminium, nitrogen-dual-doped reduced graphene oxide Co-existing with cobalt-encapsulated graphitic carbon nanotube as an activity modulated electrocatalyst for oxygen electrocatalyst for oxygen electrochemistry applications - Kharabe, Geeta Pandurang; Barik, Sidharth; Veeranmaril, Sudheesh Kumar; Nair, Aathira; Illathvalappil, Rajith; Yoyakki, Athira; Joshi, Kavita; Vinod, Chathakudath Prabhakaran; Kurungot, Sreekumar (Small, 2024)
There is a rising need to create high-performing, affordable electrocatalysts in the new field of oxygen electrochemistry. Here, a cost-effective, activity-modulated electrocatalyst with the capacity to trigger both the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) in an alkaline environment is presented. The catalyst (Al, Co/N-rGCNT) is made up of aluminium, nitrogen-dual-doped reduced graphene oxide sheets co-existing with cobalt-encapsulated carbon nanotube units. Based on X-ray Absorption Spectroscopy (XAS) studies, it is established that the superior reaction kinetics in Al, Co/N-rGCNT over their bulk counterparts can be attributed to their electronic regulation. The Al, Co/N-rGCNT performs as a versatile bifunctional electrocatalyst for zinc-air battery (ZAB), delivering an open circuit potential approximate to 1.35 V and peak power density of 106.3 mW cm-2, which are comparable to the system based on Pt/C. The Al, Co/N-rGCNT-based system showed a specific capacity of 737 mAh gZn-1 compared to 696 mAh gZn-1 delivered by the system based on Pt/C. The DFT calculations indicate that the adsorption of Co in the presence of Al doping in NGr improves the electronic properties favoring ORR. Thus, the Al, Co/N-rGCNT-based rechargeable ZAB (RZAB) emerges as a highly viable and affordable option for the development of RZAB for practical applications. This manuscript reports the development of a new bifunctional catalyst that exhibits high activity and stability under practical operating conditions. The catalyst (Al, Co/N-rGCNT) is made up of aluminium, nitrogen-dual-doped reduced graphene oxide sheets co-existing with the in situ formed cobalt-encapsulated CNT units is synthesized by a scalable pyrolysis method in an inert Ar atmosphere. The developed electrocatalyst achieved enhanced the oxygen reduction reaction (ORR) and the oxygen evolution reaction OER activity as a result of the favorable synergistic modulations and the system can serve as a process-friendly air-electrode for rechargeable zinc-air battery (RZAB). image
Keywords: Al; Bifunctional catalyst; DFT study; encapsulated structure; N-dual doping; Oxygen Evolution Reaction; oxygen reduction reaction; rechargeable zinc-air battery; X-ray absorption spectroscopy

Hydrogel electrolyte-mediated in situ Zn-anode modification and the Ru-RuO2/NGr-coated cathode for high-performance solid-state rechargeable Zn-air batteries - Kharabe, Geeta Pandurang; Verma, Tushar; Barik, Sidharth; Urkude, Rajashri R.; Ayasha, Nadeema; Ghosh, Biplab; Krishnamurty, Sailaja; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2025)
This work aims to deal with the challenges associated with designing complementary bifunctional electrocatalysts and a separator/membrane that enables rechargeable zinc-air batteries (RZABs) with nearly solid-state operability. This solid-state RZAB was accomplished by integrating a bifunctional electrocatalyst based on Ru-RuO2 interface nanoparticles supported on nitrogen-doped (N-doped) graphene (Ru-RuO2/NGr) and a dual-doped poly(acrylic acid) hydrogel (d-PAA) electrolyte soaked in KOH with sodium stannate additive. The catalyst shows enhanced activity and stability toward the two oxygen reactions, i.e., oxygen reduction and evolution reactions (ORR and OER), with a very low potential difference (Delta E) of 0.64 V. The computational insights bring out the electronic factors contributing to the enhanced catalytic activity of Ru-RuO2/NGr based on the charge density difference (CDD) between the interfaces. The disadvantages of the existing solid-state RZABs, such as their limited lifespan brought on by passivation, dendritic growth, corrosion, and shape change, have also been taken into account. The introduction of the stannate additive to the electrolyte induced an in situ Zn-anode modification, which subsequently improved the interfacial stability of the ZABs and, hence, the battery life cycles. The experimental observations reveal that, during the charging process, the Sn nanoparticles enable the homogeneous Zn deposition on the surface of the anode. Thus, the in situ Zn-anode surface modification assisted in achieving a high-rate cycle capability, viz., the homemade catalyst-based system exhibited continuous charge-discharge cycles for 20 h at a current density of 2.0 mA cm-2, with each cycle lasting for 5 min.
Keywords: Bifunctional Electrocatalyst; Core-ShellStructure; DFT study; electrolyte additive; Hydrogel; solid-state rechargeable zinc-airbattery; X-ray absorption spectroscopy